2023
DOI: 10.1177/17835917231180837
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the adoption of electric vehicles: A case study of four Indian states

Abstract: Rapid growth in petrol and diesel-powered vehicles has resulted in significant increases in tailpipe greenhouse gas emissions and air pollution, both of which harm public health in Indian cities. Furthermore, India’s dependence on imported fuel to transport people and goods threatens its fuel security. Therefore, electric mobility has been sought to deal with these issues. The governments have framed several plans and policies to promote electric vehicles (EVs) and achieve the target of EV30@30. However, EV ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They too find limitations in charging infrastructure to be a big challenge towards penetration, as do S. Mishra et al (2021). Saw & Kedia (2023) carried out a case study in Delhi, UP, Gujarat and Karnataka and found that in order to achieve a penetration of 30% EVs, by 2030 these states would need to register 0.31, 1.51, 0.88 & 0.79 million EVs. Digalwar & Rastogi (2023) demonstrate reluctance for EV adoption amongst those who place a premium on the vehicle performance.…”
Section: Barriers and Adoption Of Evsmentioning
confidence: 99%
“…They too find limitations in charging infrastructure to be a big challenge towards penetration, as do S. Mishra et al (2021). Saw & Kedia (2023) carried out a case study in Delhi, UP, Gujarat and Karnataka and found that in order to achieve a penetration of 30% EVs, by 2030 these states would need to register 0.31, 1.51, 0.88 & 0.79 million EVs. Digalwar & Rastogi (2023) demonstrate reluctance for EV adoption amongst those who place a premium on the vehicle performance.…”
Section: Barriers and Adoption Of Evsmentioning
confidence: 99%